Active metal material surface functional coating and additive and subtractive precise preparation method thereof
By combining ultrafast laser fixed-point subtraction and SLM technology, the nanoparticles are accurately deposited, which solves the problems of poor wear and corrosion resistance and insufficient antibacterial function in the surface treatment technology of active metal materials, and achieves efficient coating preparation and functional expression, meeting the application needs of the medical field.
Patent Information
- Application Number
- CN202510037116.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2045-01-09
AI Technical Summary
The existing surface treatment technology of active metal materials has poor wear and corrosion resistance, insufficient antibacterial function, and coating adhesion, uneven thickness and porosity, which limits its application in the medical field.
Using alternating ultrafast laser fixed-point subtraction and SLM technology, the coating is accurately deposited by processing microstructures on the substrate surface and uniformly mixing nanoparticles with micropowder to accurately deposit the coating to achieve the precise distribution and functional expression of the coating phase and nanoparticles.
It significantly improves the wear and corrosion resistance of the surface of active metal materials, and realizes the expression of antibacterial properties, meeting the application needs of high-end medical and other fields.
Smart Images

Figure CN119549747A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal material preparation, and in particular to a method for accurately preparing a functional coating on the surface of an active metal material and an additive and subtractive coating. Background Art
[0002] Active metals, such as titanium alloys, magnesium alloys and zinc alloys, are widely used in medical devices and other fields because of their low density, high strength and good biological properties. However, the corrosion resistance of active metal surfaces is poor. After being corroded, the mechanical properties will drop sharply, and fractures will occur at any corrosion point, resulting in device failure. At the same time, bone implants made of traditional active metals will have infection problems after surgery, or cause inflammation due to surface wear and peeling of corrosion products, which will affect human health and greatly limit the application of traditional active metal materials. Therefore, it is urgent to design and prepare wear-resistant, corrosion-resistant and antibacterial functional coatings for the surface of traditional active metal materials. Existing surface treatment technologies, such as chemical plating, electroplating and thermal spraying, can improve the surface properties of active metals to a certain extent, but in practical applications, there are still problems such as insufficient coating adhesion, uneven thickness and high porosity, which limit the preparation effect and use efficacy of active metal surface coatings. Therefore, it is urgent to design and develop new magnesium alloy protective coating preparation technologies.
[0003] Laser Additive Manufacturing (LAM) is an emerging material preparation method that can rapidly form a coating of a certain thickness on the surface of a part by accumulating layer by layer, ensuring that the interface is metallurgically bonded while giving the surface the special properties required for the application. Based on this, in order to meet the target performance required by the part, researchers often mechanically mix some nano or micro ceramic particles with metal powders, and then deposit them layer by layer through LAM to achieve the specific needs of metal parts in the target occasion. It often includes powder feeding additive methods, namely laser cladding (LC), and powder spreading additive methods, namely laser selective melting (SLM).
[0004] Although the Chinese invention patent application with publication number CN110729391A, "Method, device and thermoelectric material block for preparing magnesium silicide thermoelectric material block", uses magnesium silicide and pure magnesium powder as LAM powder raw materials, and adopts the powder feeding additive method, namely the LC process, to directly form a magnesium silicide thermoelectric material block with thermoelectric properties, it adopts a mechanical powder mixing method, and the size and distribution of the phases inside the prepared parts cannot be strictly controlled; the Chinese invention patent application with publication number CN115041678A, "A micro-nanostructured high-activity spherical aluminum alloy The Chinese invention patent application CN115156525A, entitled "An active modified spherical magnesium alloy powder based on electrostatic self-assembly and its preparation method and application", proposed a method of first performing surface nano-modification on micron powder and then performing LAM forming. However, in actual operation, the nanoparticles modified on the surface of micron powder cannot be accurately quantified, and it is even more impossible to achieve accurate distribution inside the formed part after LAM forming. The various phases formed in situ will also be randomly distributed under the driving force of Marangoni force. Therefore, how to accurately and quantitatively control the precise forming and controllable distribution of different types of phases in the final part is one of the key issues that need to be solved at this stage, and it is also a technical difficulty that restricts the effective performance of the designed material.
[0005] Ultrafast laser micro-nano processing is a new type of subtractive technology that uses high-energy pulse burning to accurately cut surfaces such as titanium and magnesium alloys. It is currently commonly used in SLM to remove residual powder on the side. How to use ultrafast laser micro-nano processing and the layer-by-layer deposition preparation characteristics of SLM technology to achieve accurate preparation of multifunctional coatings on active metal surfaces and transform the multifunctional design effects of coatings into precise forming from a preparation perspective is an important problem that needs to be solved at this stage.
[0006] The Chinese invention patent application with publication number CN118371729A, "A method for additive and subtractive composite forming of an amorphous alloy", discloses a method for obtaining an amorphous alloy through ultrafast laser micro-nano processing and SLM, so that the amorphous alloy powder is connected to the amorphous alloy substrate in a bonding manner, and the new printed layer has a better fusion effect with the previous layer, thereby reducing the formation of internal defects and effectively improving the internal effect of the amorphous alloy. However, this method improves the alloy performance by reducing the formation of internal defects, and does not enhance the performance of active metals. The wear and corrosion resistance still needs to be further improved, and the amorphous alloy does not have biological activity and cannot meet the application needs in the medical field.
[0007] Therefore, it is of great significance to develop a functional coating on the surface of active metal materials with excellent wear resistance and corrosion resistance and suitable for application requirements in the medical field and a preparation method thereof. Summary of the invention
[0008] In view of the fact that the existing alloy material additive and subtractive composite forming methods have the problems that the wear and corrosion resistance effects still need to be further improved, and they do not have biological activity and cannot meet the application requirements in the medical field, the present invention provides a functional coating on the surface of an active metal material and a preparation method thereof, which can significantly improve the surface wear resistance and corrosion resistance of active metals such as titanium, magnesium, and zinc alloys, while helping them to express functionality such as antibacterial properties, thereby meeting their application requirements in high-end medical and other fields, and providing new possibilities for expanding the application of active metals in various fields.
[0009] To achieve the above object, the technical solution adopted by the present invention is:
[0010] A method for accurately preparing a functional coating on the surface of an active metal material by adding or subtracting materials, comprising the following steps:
[0011] S1. Select micron powder with a particle size of 20 to 75 μm and nanoparticles with a particle size of 10 to 500 nm, mix them evenly, vacuum dry them, and set aside;
[0012] S2. Processing microstructures on the substrate surface using an ultrafast laser; the ultrafast laser power is 10 to 60 W, the pulse frequency is 5 to 50 kHz, and the travel speed is 100 to 500 cm / s;
[0013] S3. The mixed powder obtained in S1 is laid on the surface of the substrate obtained in S2, evenly laid in a manner to fill the microstructure, and formed by SLM continuous laser; the SLM continuous laser power is 50 to 150 W, the scanning speed is 100 to 800 mm / s, and the scanning interval is 0.03 to 0.05 mm;
[0014] S4. Repeat the above steps S2 and S3 until the desired coating thickness is reached, thereby obtaining the functional coating on the surface of the active metal material.
[0015] Furthermore, the ratio of the micron powder and the nanoparticles in S1 is (80-95):(5-20).
[0016] Furthermore, the sphericity of the micron powder in S1 is ≥85%.
[0017] Furthermore, the uniform mixing in S1 is performed by planetary ball milling; the planetary ball milling mixing time is 0.5 to 1.5 hours, the rotation speed is 100 to 300 r / min, and the ball-to-material mass ratio is (1 to 5):1.
[0018] Furthermore, in addition to filling 1 / 2 to 1 / 3 of the tank volume with anhydrous ethanol (purity 99.9%) as a liquid medium, the remaining tank volume is filled with high-purity argon gas to avoid problems such as oxidation and powder adhesion during the ball milling process.
[0019] Furthermore, the vacuum drying temperature in S1 is 100 to 200° C., and the pressure is -0.08 to -0.1 MPa.
[0020] Furthermore, the ultrafast laser in S2 is a femtosecond laser and / or a picosecond laser.
[0021] Furthermore, the ultrafast laser described in S2 is a femtosecond laser. Since the heat-affected zone after femtosecond laser processing is extremely small, there are no fine cracks, the surface physical properties change little, and the processed holes are deep pit-shaped, the nanoparticles can be shaken in well and are not easily pulled out during multiple powder coatings.
[0022] Furthermore, the substrate in S2 is an active metal substrate; the active metal is one or more of titanium-based materials, magnesium-based materials, iron-based materials, and zinc-based materials.
[0023] Furthermore, the substrate is a conventionally prepared substrate, and its surface needs to be ground, polished and cleaned with alcohol until it reaches a mirror surface.
[0024] Furthermore, if the substrate is an SLM substrate formed directly in the device, an ultrafast laser is used to quickly scan its surface; the ultrafast laser power is 10 to 40 W, the pulse frequency is 5 to 50 kHz, the travel speed is 600 to 1000 cm / s, and the overlap rate is 10 to 70%.
[0025] Furthermore, the microstructure described in S2 is a dot matrix hole groove, the hole diameter is 3 to 20 μm, the depth is 1 to 5 μm, and the minimum distance between two holes is 1 hole diameter.
[0026] Furthermore, the step of spreading the mixed powder on the substrate surface in S3 is to repeatedly spread the mixed powder with a scraper to ensure that the nanoparticles can completely fall into and fill the deep pits ablated by the ultrafast laser, and at the same time, the micron powder can be evenly spread on the surface.
[0027] Furthermore, the scraper is a ceramic scraper, which can ensure that the nanoparticles that fall into the micro-pits will not be dragged out due to electrostatic force during the repeated spreading of the powder, and at the same time, the sharp ceramic scraper can well scrape off the nanoparticles attached to the micron powder.
[0028] Furthermore, after the SLM continuous laser forming in S3, the step of using an ultrafast laser to quickly scan the entire surface is also included.
[0029] Furthermore, the ultrafast laser power is 10-40W, the pulse frequency is 5-50kHz, the travel speed is 600-1000cm / s, and the overlap rate is 10-70%.
[0030] Another object of the present invention is to provide a functional coating on the surface of an active metal material.
[0031] A functional coating on the surface of an active metal material is prepared by any of the preparation methods described above.
[0032] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0033] The functional coating on the surface of the active metal material of the present invention is prepared by alternating ultrafast laser point-by-point subtraction and SLM and other technologies. A microstructure is first prepared on the target substrate to store the nano-reinforced particles shaken off during powder spreading, and then the nano-particles are precisely deposited to strengthen the target coating by SLM technology. The enrichment position of the nano-particles is precisely controlled by mechanical regulation to achieve precise regulation of the coating phase, the spatial position and distribution of the nano-particles, so that the functional nano-particles can be controllably released according to the design concept. While significantly improving the wear resistance and corrosion resistance of the active metal surface, it can help it achieve the expression of functionality such as antibacterial properties, meeting its application needs in high-end medical and other fields.
[0034] The method for preparing functional coatings on the surface of active metal materials of the present invention can directly deposit a protective layer on the surface of alloy parts formed by SLM, or the surface of the alloy block to be protected can be polished and then the coating can be prepared by this method. It is convenient, fast, simple, efficient and can be used flexibly. The prepared coating has few defects such as pores and cracks, and the grains are extremely fine. It is mainly composed of dense equiaxed crystal structure and is metallurgically bonded to the matrix. The added nanoparticles not only act as in-situ nucleating agents to promote grain refinement and dispersion strengthening, but also provide a reliable method for the controllable degradation and biological function expression of the coating due to the precise distribution of the nanoparticles inside the coating. While achieving the improvement of hardness and mechanical effects such as particle enhancement and in-situ strengthening, the controlled release of functional nanoparticles is also achieved. The resulting coating can achieve controllable thickness and metallurgical bonding. The nanoparticles are precisely distributed inside the coating according to the designer's ideas, and the required coating efficacy can be expressed in sequence according to the designer's ideas. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The invention is further described using the accompanying drawings, but the embodiments in the accompanying drawings do not constitute any limitation to the invention. A person skilled in the art can obtain other drawings based on the following drawings without creative work.
[0036] Figure 1 It is a flow chart for preparing the functional coating on the surface of the active metal material of the present invention.
[0037] Figure 2 This is a microstructure diagram of the functional coating on the surface of the active metal material in Example 1 of the present invention.
[0038] Figure 3It is a SEM picture of the active metal surface coating of Comparative Example 1 of the present invention.
[0039] Figure 4 It is a SEM picture of the active metal surface coating of Comparative Example 2 of the present invention.
[0040] Figure 5 This is a microscopic morphology of the active metal surface coating of Comparative Example 3 of the present invention.
[0041] Figure 6 It is a microscopic morphology of the active metal surface coating of comparative example 4 of the present invention.
[0042] Figure 7 This is a microscopic morphology of the active metal surface coating of Comparative Example 5 of the present invention.
[0043] Figure 8 It is a macroscopic and microscopic morphology of the active metal surface coating of comparative example 6 of the present invention.
[0044] Fig. 9 It is the cell staining picture of Example 1 of the present invention and the AZ91D sample formed by SLM.
[0045] Fig.10 It is the antibacterial effect diagram of Example 1 of the present invention and Comparative Example 7. DETAILED DESCRIPTION
[0046] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention is further described by the following examples. Obviously, the following examples are only part of the embodiments of the present invention, rather than all the embodiments; it should be understood that the embodiments of the present invention are only used to illustrate the technical effects of the present invention, rather than to limit the scope of protection of the present invention.
[0047] The raw materials in the examples can all be obtained commercially; unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0048] Example 1
[0049] A method for accurately preparing a functional coating on the surface of an active metal material by adding or subtracting materials, comprising the following steps:
[0050] S1. Weigh nanoparticles with a purity of ≥99.90wt.% and micron powder for SLM as raw materials by weight percentage, select 90wt.% AZ91D magnesium alloy micron powder with a particle size of 50μm and 10wt.% ZnO nanoparticles with a particle size of 100nm, put them into a planetary ball mill for mixing, the mixing time is selected as 1 hour, the speed is 150r / min, the ball-to-material mass ratio is 2:1, and the spherical tank is filled with 1 / 2 volume of anhydrous ethanol (purity ≥99vol.%) and 1 / 2 volume of high-purity argon (purity ≥99.999vol.%) in the spherical tank. The mixed target powder is placed in a vacuum drying oven for high-temperature and vacuum drying. The drying temperature is set to 150°C, the vacuum pressure is set to -0.1MPa, the heating rate is 80°C / min, the insulation time is 1h, and then the temperature is reduced to 25°C for storage. The obtained powder material is placed in a vacuum bag and vacuumed for storage for standby use;
[0051] S2. The SLM method is used to first form the AZ91D magnesium alloy, and then the ultrafast laser is used to remove the surface powder on the entire substrate. The ultrafast laser power is 20W, the pulse frequency is 10kHz, the travel speed is 800cm / s, and the overlap rate is 50%. The femtosecond laser is used to process the dot matrix holes on the surface of the AZ91D magnesium alloy substrate. The hole diameter is 10μm, the depth is 3μm, and the minimum spacing between two holes is 1 hole diameter. The femtosecond laser power is 30W, the pulse frequency is 20kHz, and the travel speed is 200cm / s.
[0052] S3. The mixed powder obtained by S1 is spread on the surface of the substrate obtained by S2, and is spread evenly in a manner of filling the microstructure. A ceramic scraper is used to repeatedly spread the mixed powder to ensure that the nanoparticles can completely fall into and fill the deep pits ablated by the ultrafast laser. At the same time, the micron powder can also be evenly spread on the surface of the substrate to be protected. The thickness of each layer of powder is set at 40μm. SLM continuous laser is used for forming, and the scanning strategy is selected as a zigzag scanning mode; the SLM continuous laser power is 100W, the scanning speed is 500mm / s, and the scanning interval is 0.04mm; an ultrafast laser is used for full-width rapid scanning to smooth the SLM surface. The ultrafast laser power is 20W, the pulse frequency is 10kHz, the walking speed is 800cm / s, and the overlap rate is 50%;
[0053] S4. Repeat the above steps S2 and S3 until the desired coating thickness is reached, thereby obtaining the functional coating on the surface of the active metal material.
[0054] Example 2
[0055] A method for accurately preparing a functional coating on the surface of an active metal material by adding or subtracting materials, comprising the following steps:
[0056] S1. Weigh nanoparticles with a purity of ≥99.90wt.% and micron powder for SLM as raw materials by weight percentage, select 90wt.% AZ91D magnesium alloy micron powder with a particle size of 40μm and 10wt.% ZnO nanoparticles with a particle size of 200nm, put them into a planetary ball mill for mixing, the mixing time is selected as 1 hour, the speed is 150r / min, the ball-to-material mass ratio is 2:1, and the spherical tank is filled with 1 / 2 volume of anhydrous ethanol (purity ≥99vol.%) and 1 / 2 volume of high-purity argon (purity ≥99.999vol.%) in the spherical tank. The mixed target powder is placed in a vacuum drying oven for high-temperature and vacuum drying. The drying temperature is set to 150°C, the vacuum pressure is set to -0.1MPa, the heating rate is 80°C / min, the insulation time is 1h, and then the temperature is reduced to 25°C for storage. The obtained powder material is placed in a vacuum bag and vacuumed for storage for standby use;
[0057] S2. A cast AZ91D magnesium alloy substrate was directly polished to a mirror surface and placed in an SLM molding chamber; a femtosecond laser was used to process dot matrix holes on the surface of the AZ91D magnesium alloy substrate, with a hole diameter of 10 μm, a depth of 3 μm, and a minimum spacing between two holes of 1 hole diameter; the femtosecond laser power was 20 W, the pulse frequency was 10 kHz, and the travel speed was 500 cm / s;
[0058] S3. The mixed powder obtained in S1 is spread on the surface of the substrate obtained in S2, and is spread evenly in a manner of filling the microstructure. A ceramic scraper is used to repeatedly spread the mixed powder to ensure that the nanoparticles can completely fall into and fill the deep pits ablated by the ultrafast laser. At the same time, the micron powder can also be evenly spread on the surface of the substrate to be protected. The thickness of each layer of powder is set at 40μm. SLM continuous laser is used for forming, and the scanning strategy is selected as a zigzag scanning mode; the SLM continuous laser power is 80W, the scanning speed is 600mm / s, and the scanning interval is 0.045mm; an ultrafast laser is used for full-width rapid scanning to smooth the SLM surface. The ultrafast laser power is 10W, the pulse frequency is 20kHz, the walking speed is 600cm / s, and the overlap rate is 60%;
[0059] S4. Repeat the above steps S2 and S3 until the desired coating thickness is reached, thereby obtaining the functional coating on the surface of the active metal material.
[0060] Example 3
[0061] A method for accurately preparing a functional coating on the surface of an active metal material by adding or subtracting materials, comprising the following steps:
[0062] S1. Weigh nanoparticles with a purity of ≥99.90wt.% and micron powder for SLM as raw materials by weight percentage, select 85wt.% WE43 magnesium powder with a particle size of 40μm and 15wt.% CuO nanoparticles with a particle size of 200nm, put them into a planetary ball mill for mixing, the mixing time is selected as 1 hour, the speed is 150r / min, the ball-to-material mass ratio is 2:1, and the spherical tank is filled with 1 / 2 volume of anhydrous ethanol (purity ≥99vol.%) and 1 / 2 volume of high-purity argon (purity ≥99.999vol.%) of the spherical tank. The mixed target powder is placed in a vacuum drying oven for high-temperature and vacuum drying. The drying temperature is set to 150°C, the vacuum pressure is set to -0.1MPa, the heating rate is 80°C / min, the insulation time is 1h, and then the temperature is reduced to 25°C for storage. The obtained powder material is placed in a vacuum bag and vacuumed for storage for standby use;
[0063] S2. The SLM method is used to first form the AZ91D magnesium alloy, and then the ultrafast laser is used to remove the surface powder on the entire substrate. The ultrafast laser power is 20W, the pulse frequency is 10kHz, the travel speed is 800cm / s, and the overlap rate is 50%. The femtosecond laser is used to process the dot matrix holes on the surface of the AZ91D magnesium alloy substrate. The hole diameter is 15μm, the depth is 4μm, and the minimum spacing between two holes is 1 hole diameter. The femtosecond laser power is 30W, the pulse frequency is 20kHz, and the travel speed is 200cm / s.
[0064] S3. The mixed powder obtained by S1 is spread on the surface of the substrate obtained by S2, and is spread evenly in a manner of filling the microstructure. A ceramic scraper is used to repeatedly spread the mixed powder to ensure that the nanoparticles can completely fall into and fill the deep pits ablated by the ultrafast laser. At the same time, the micron powder can also be evenly spread on the surface of the substrate to be protected. The thickness of each layer of powder is set at 40μm. SLM continuous laser is used for forming, and the scanning strategy is selected as a zigzag scanning mode; the SLM continuous laser power is 100W, the scanning speed is 500mm / s, and the scanning interval is 0.04mm; an ultrafast laser is used for full-width rapid scanning to smooth the SLM surface. The ultrafast laser power is 20W, the pulse frequency is 10kHz, the walking speed is 800cm / s, and the overlap rate is 50%;
[0065] S4. Repeat the above steps S2 and S3 until the desired coating thickness is reached, thereby obtaining the functional coating on the surface of the active metal material.
[0066] Example 4
[0067] A method for accurately preparing a functional coating on the surface of an active metal material by adding or subtracting materials, comprising the following steps:
[0068] S1. Weigh nanoparticles with a purity of ≥99.90wt.% and micron powder for SLM as raw materials by weight percentage, select 85wt.% WE43 magnesium powder with a particle size of 40μm and 15wt.% CuO nanoparticles with a particle size of 200nm, put them into a planetary ball mill for mixing, the mixing time is selected as 1 hour, the speed is 150r / min, the ball-to-material mass ratio is 2:1, and the spherical tank is filled with 1 / 2 volume of anhydrous ethanol (purity ≥99vol.%) and 1 / 2 volume of high-purity argon (purity ≥99.999vol.%) of the spherical tank. The mixed target powder is placed in a vacuum drying oven for high-temperature and vacuum drying. The drying temperature is set to 150°C, the vacuum pressure is set to -0.1MPa, the heating rate is 80°C / min, the insulation time is 1h, and then the temperature is reduced to 25°C for storage. The obtained powder material is placed in a vacuum bag and vacuumed for storage for standby use;
[0069] S2. A cast AZ91D magnesium alloy substrate was directly polished to a mirror surface and placed in an SLM molding chamber; a femtosecond laser was used to process dot matrix holes on the surface of the AZ91D magnesium alloy substrate, with a hole diameter of 8 μm, a depth of 2 μm, and a minimum spacing between two holes of 1 hole diameter; the femtosecond laser power was 20 W, the pulse frequency was 10 kHz, and the travel speed was 500 cm / s;
[0070] S3. The mixed powder obtained in S1 is spread on the surface of the substrate obtained in S2, and is spread evenly in a manner of filling the microstructure. A ceramic scraper is used to repeatedly spread the mixed powder to ensure that the nanoparticles can completely fall into and fill the deep pits ablated by the ultrafast laser. At the same time, the micron powder can also be evenly spread on the surface of the substrate to be protected. The thickness of each layer of powder is set at 40μm. SLM continuous laser is used for forming, and the scanning strategy is selected as a zigzag scanning mode; the SLM continuous laser power is 80W, the scanning speed is 600mm / s, and the scanning interval is 0.045mm; an ultrafast laser is used for full-width rapid scanning to smooth the SLM surface. The ultrafast laser power is 10W, the pulse frequency is 20kHz, the walking speed is 600cm / s, and the overlap rate is 60%;
[0071] S4. Repeat the above steps S2 and S3 until the desired coating thickness is reached, thereby obtaining the functional coating on the surface of the active metal material.
[0072] Comparative Example 1
[0073] A method for accurately preparing an active metal surface coating by adding or subtracting materials comprises the following steps:
[0074] S1. Weigh nanoparticles with a purity of ≥99.90wt.% and micron powder for SLM as raw materials by weight percentage, select 85wt.% WE43 magnesium powder with a particle size of 40μm and 15wt.% CuO nanoparticles with a particle size of 200nm, put them into a planetary ball mill for mixing, the mixing time is selected as 1 hour, the speed is 150r / min, the ball-to-material mass ratio is 2:1, and the spherical tank is filled with 1 / 2 volume of anhydrous ethanol (purity ≥99vol.%) and 1 / 2 volume of high-purity argon (purity ≥99.999vol.%) of the spherical tank. The mixed target powder is placed in a vacuum drying oven for high-temperature and vacuum drying. The drying temperature is set to 150°C, the vacuum pressure is set to -0.1MPa, the heating rate is 80°C / min, the insulation time is 1h, and then the temperature is reduced to 25°C for storage. The obtained powder material is placed in a vacuum bag and vacuumed for storage for standby use;
[0075] S2. The mixed powder obtained in S1 is laid on the surface of the cast AZ91D magnesium alloy substrate, and SLM continuous laser is used for forming. The scanning strategy is selected as a zigzag scanning mode; the SLM continuous laser power is 100W, the scanning speed is 500mm / s, and the scanning interval is 0.04mm; an ultrafast laser is used for full-width fast scanning to smooth the SLM surface. The ultrafast laser power is 20W, the pulse frequency is 10kHz, the walking speed is 800cm / s, the overlap rate is 50%, and the coating is formed to the required coating thickness to obtain the active metal surface coating.
[0076] Compared with Example 1, the main difference of this comparative example is that the ultrafast laser fixed-point material reduction step is not performed.
[0077] Comparative Example 2
[0078] A method for accurately preparing an active metal surface coating by adding or subtracting materials comprises the following steps:
[0079] S1. Weigh nanoparticles with a purity of ≥99.90wt.% and micron powder for SLM as raw materials by weight percentage, select 90wt.% pure Zn micron powder with a particle size of 10μm and 10wt.% ZnO nanoparticles with a particle size of 200nm, put them into a planetary ball mill for mixing, the mixing time is selected as 1 hour, the speed is 150r / min, the ball-to-material mass ratio is 2:1, and the spherical tank is filled with 1 / 2 volume of anhydrous ethanol (purity ≥99vol.%) and 1 / 2 volume of high-purity argon (purity ≥99.999vol.%) of the spherical tank. The mixed target powder is placed in a vacuum drying oven for high-temperature and vacuum drying. The drying temperature is set to 150°C, the vacuum pressure is set to -0.1MPa, the heating rate is 80°C / min, the insulation time is 1h, and then the temperature is reduced to 25°C for storage. The obtained powder material is placed in a vacuum bag for vacuum storage and standby;
[0080] S2. A cast AZ91D magnesium alloy substrate was directly polished to a mirror surface and placed in an SLM molding chamber; a femtosecond laser was used to process dot matrix holes on the surface of the AZ91D magnesium alloy substrate, with a hole diameter of 10 μm, a depth of 3 μm, and a minimum spacing between two holes of 1 hole diameter; the femtosecond laser power was 30 W, the pulse frequency was 10 kHz, and the travel speed was 500 cm / s;
[0081] S3. The mixed powder obtained in S1 is spread on the surface of the substrate obtained in S2, and is spread evenly in a manner of filling the microstructure. A ceramic scraper is used to repeatedly spread the mixed powder to ensure that the nanoparticles can completely fall into and fill the deep pits ablated by the ultrafast laser. At the same time, the micron powder can also be evenly spread on the surface of the substrate to be protected. The thickness of each layer of powder is set at 40μm. SLM continuous laser is used for forming, and the scanning strategy is selected as a zigzag scanning mode; the SLM continuous laser power is 80W, the scanning speed is 600mm / s, and the scanning interval is 0.045mm; an ultrafast laser is used for full-width rapid scanning to smooth the SLM surface, the ultrafast laser power is 10W, the pulse frequency is 20kHz, the walking speed is 600cm / s, and the overlap rate is 60%;
[0082] S4. Repeat the above steps S2 and S3 until the desired coating thickness is reached, thereby obtaining the active metal surface coating.
[0083] Compared with Example 1, the main difference of this comparative example is that the particle size of the micron powder is too small.
[0084] Comparative Example 3
[0085] A method for accurately preparing an active metal surface coating by adding or subtracting materials comprises the following steps:
[0086] S1. Weigh nanoparticles with a purity of ≥99.90wt.% and micron powder for SLM as raw materials by weight percentage, select 85wt.% WE43 magnesium powder with a particle size of 40μm and 15wt.% CuO nanoparticles with a particle size of 900nm, put them into a planetary ball mill for mixing, the mixing time is selected as 1 hour, the speed is 150r / min, the ball-to-material mass ratio is 2:1, and the spherical tank is filled with 1 / 2 volume of anhydrous ethanol (purity ≥99vol.%) and 1 / 2 volume of high-purity argon (purity ≥99.999vol.%) of the spherical tank. The mixed target powder is placed in a vacuum drying oven for high-temperature and vacuum drying. The drying temperature is set to 150°C, the vacuum pressure is set to -0.1MPa, the heating rate is 80°C / min, the insulation time is 1h, and then the temperature is reduced to 25°C for storage. The obtained powder material is placed in a vacuum bag and vacuumed for storage for standby use;
[0087] S2. A cast AZ91D magnesium alloy substrate was directly polished to a mirror surface and placed in an SLM molding chamber; a femtosecond laser was used to process dot matrix holes on the surface of the AZ91D magnesium alloy substrate, with a hole diameter of 10 μm, a depth of 3 μm, and a minimum spacing between two holes of 1 hole diameter; the femtosecond laser power was 30 W, the pulse frequency was 20 kHz, and the travel speed was 200 cm / s;
[0088] S3. The mixed powder obtained by S1 is spread on the surface of the substrate obtained by S2, and is spread evenly in a manner of filling the microstructure. A ceramic scraper is used to repeatedly spread the mixed powder to ensure that the nanoparticles can completely fall into and fill the deep pits ablated by the ultrafast laser. At the same time, the micron powder can also be evenly spread on the surface of the substrate to be protected. The thickness of each layer of powder is set at 40μm. SLM continuous laser is used for forming, and the scanning strategy is selected as a zigzag scanning method; the SLM continuous laser power is 100W, the scanning speed is 500mm / s, and the scanning interval is 0.04mm; an ultrafast laser is used for full-width rapid scanning to smooth the SLM surface. The ultrafast laser power is 20W, the pulse frequency is 10kHz, the walking speed is 800cm / s, and the overlap rate is 50%.
[0089] S4. Repeat the above steps S2 and S3 until the desired coating thickness is reached, thereby obtaining the active metal surface coating.
[0090] Compared with Example 1, the main difference of this comparative example is that the particle size of the nanoparticles is too large.
[0091] Comparative Example 4
[0092] A method for accurately preparing an active metal surface coating by adding or subtracting materials comprises the following steps:
[0093] S1. Weigh nanoparticles with a purity of ≥99.90wt.% and micron powder for SLM as raw materials by weight percentage, select 90wt.% pure Zn micron powder with a particle size of 40μm and 10wt.% ZnO nanoparticles with a particle size of 200nm, put them into a planetary ball mill for mixing, the mixing time is selected as 1 hour, the speed is 150r / min, the ball-to-material mass ratio is 2:1, and the spherical tank is filled with 1 / 2 volume of anhydrous ethanol (purity ≥99vol.%) and 1 / 2 volume of high-purity argon (purity ≥99.999vol.%) of the spherical tank. The mixed target powder is placed in a vacuum drying oven for high-temperature and vacuum drying. The drying temperature is set to 150°C, the vacuum pressure is set to -0.1MPa, the heating rate is 80°C / min, the insulation time is 1h, and then the temperature is reduced to 25°C for storage. The obtained powder material is placed in a vacuum bag and vacuumed for storage for standby use;
[0094] S2. A cast AZ91D magnesium alloy substrate was directly polished to a mirror surface and placed in an SLM molding chamber; a femtosecond laser was used to process dot matrix holes on the surface of the AZ91D magnesium alloy substrate, with a hole diameter of 10 μm, a depth of 3 μm, and a minimum spacing between two holes of 1 hole diameter; the femtosecond laser power was 5 W, the pulse frequency was 1 kHz, and the travel speed was 600 cm / s;
[0095] S3. The mixed powder obtained in S1 is spread on the surface of the substrate obtained in S2, and is spread evenly in a manner of filling the microstructure. A ceramic scraper is used to repeatedly spread the mixed powder to ensure that the nanoparticles can completely fall into and fill the deep pits ablated by the ultrafast laser. At the same time, the micron powder can also be evenly spread on the surface of the substrate to be protected. The thickness of each layer of powder is set at 40μm. SLM continuous laser is used for forming, and the scanning strategy is selected as a zigzag scanning mode; the SLM continuous laser power is 80W, the scanning speed is 600mm / s, and the scanning interval is 0.045mm; an ultrafast laser is used for full-width rapid scanning to smooth the SLM surface. The ultrafast laser power is 10W, the pulse frequency is 20kHz, the walking speed is 600cm / s, and the overlap rate is 60%;
[0096] S4. Repeat the above steps S2 and S3 until the desired coating thickness is reached, thereby obtaining the active metal surface coating.
[0097] Compared with Example 1, the main difference of this comparative example is that the ultrafast laser power and pulse frequency are too small.
[0098] Comparative Example 5
[0099] A method for accurately preparing an active metal surface coating by adding or subtracting materials comprises the following steps:
[0100] S1. Weigh nanoparticles with a purity of ≥99.90wt.% and micron powder for SLM as raw materials by weight percentage, select 90wt.% pure Zn micron powder with a particle size of 40μm and 10wt.% ZnO nanoparticles with a particle size of 200nm, put them into a planetary ball mill for mixing, the mixing time is selected as 1 hour, the speed is 150r / min, the ball-to-material mass ratio is 2:1, and the spherical tank is filled with 1 / 2 volume of anhydrous ethanol (purity ≥99vol.%) and 1 / 2 volume of high-purity argon (purity ≥99.999vol.%) of the spherical tank. The mixed target powder is placed in a vacuum drying oven for high-temperature and vacuum drying. The drying temperature is set to 150°C, the vacuum pressure is set to -0.1MPa, the heating rate is 80°C / min, the insulation time is 1h, and then the temperature is reduced to 25°C for storage. The obtained powder material is placed in a vacuum bag and vacuumed for storage for standby use;
[0101] S2. A cast AZ91D magnesium alloy substrate was directly polished to a mirror surface and placed in an SLM molding chamber; a femtosecond laser was used to process dot matrix holes on the surface of the AZ91D magnesium alloy substrate, with a hole diameter of 10 μm, a depth of 3 μm, and a minimum spacing between two holes of 1 hole diameter; the femtosecond laser power was 50 W, the pulse frequency was 60 kHz, and the travel speed was 600 cm / s;
[0102] S3. The mixed powder obtained in S1 is spread on the surface of the substrate obtained in S2, and is spread evenly in a manner of filling the microstructure. A ceramic scraper is used to repeatedly spread the mixed powder to ensure that the nanoparticles can completely fall into and fill the deep pits ablated by the ultrafast laser. At the same time, the micron powder can also be evenly spread on the surface of the substrate to be protected. The thickness of each layer of powder is set at 40μm. SLM continuous laser is used for forming, and the scanning strategy is selected as a zigzag scanning mode; the SLM continuous laser power is 80W, the scanning speed is 600mm / s, and the scanning interval is 0.045mm; an ultrafast laser is used for full-width rapid scanning to smooth the SLM surface. The ultrafast laser power is 10W, the pulse frequency is 20kHz, the walking speed is 600cm / s, and the overlap rate is 60%;
[0103] S4. Repeat the above steps S2 and S3 until the desired coating thickness is reached, thereby obtaining the active metal surface coating.
[0104] Compared with Example 1, the main difference of this comparative example is that the ultrafast laser power and pulse frequency are too large.
[0105] Comparative Example 6
[0106] A method for accurately preparing an active metal surface coating by adding or subtracting materials comprises the following steps:
[0107] S1. Weigh nanoparticles with a purity of ≥99.90wt.% and micron powder for SLM as raw materials by weight percentage, select 90wt.% pure Zn micron powder with a particle size of 50μm and 10wt.% ZnO nanoparticles with a particle size of 100nm, put them into a planetary ball mill for mixing, the mixing time is selected as 1 hour, the speed is 150r / min, the ball-to-material mass ratio is 2:1, and the spherical tank is filled with 1 / 2 volume of anhydrous ethanol (purity ≥99vol.%) and 1 / 2 volume of high-purity argon (purity ≥99.999vol.%) of the spherical tank. The mixed target powder is placed in a vacuum drying oven for high-temperature and vacuum drying. The drying temperature is set to 150°C, the vacuum pressure is set to -0.1MPa, the heating rate is 80°C / min, the insulation time is 1h, and then the temperature is reduced to 25°C for storage. The obtained powder material is placed in a vacuum bag and vacuumed for storage for standby use;
[0108] S2. A cast AZ91D magnesium alloy substrate was directly polished to a mirror surface and placed in an SLM molding chamber; a femtosecond laser was used to process dot matrix holes on the surface of the AZ91D magnesium alloy substrate, with a hole diameter of 10 μm, a depth of 3 μm, and a minimum spacing between two holes of 1 hole diameter; the femtosecond laser power was 30 W, the pulse frequency was 20 kHz, and the travel speed was 200 cm / s;
[0109] S3. The mixed powder obtained by S1 is spread on the surface of the substrate obtained by S2, and is spread evenly in a manner of filling the microstructure. A ceramic scraper is used to repeatedly spread the mixed powder to ensure that the nanoparticles can completely fall into and fill the deep pits ablated by the ultrafast laser. At the same time, the micron powder can also be evenly spread on the surface of the substrate to be protected. The thickness of each layer of powder is set at 40μm. SLM continuous laser is used for forming, and the scanning strategy is selected as a zigzag scanning method; the SLM continuous laser power is 200W, the scanning speed is 50mm / s, and the scanning interval is 0.02mm; an ultrafast laser is used for full-width rapid scanning to smooth the SLM surface. The ultrafast laser power is 20W, the pulse frequency is 10kHz, the walking speed is 800cm / s, and the overlap rate is 50%.
[0110] S4. Repeat the above steps S2 and S3 until the desired coating thickness is reached, thereby obtaining the active metal surface coating.
[0111] Compared with Example 1, the main difference of this comparative example is that the SLM continuous laser power and scanning speed are too large.
[0112] Comparative Example 7
[0113] A method for accurately preparing an active metal surface coating by adding or subtracting materials comprises the following steps:
[0114] S1. Weigh the SLM micron powder with a purity of ≥99.90wt.% as the raw material, select the AZ91D magnesium alloy micron powder with a particle size of 20μm, put it into a planetary ball mill for mixing, the mixing time is selected as 1 hour, the speed is 150r / min, the ball-to-material mass ratio is 2:1, and the spherical tank is filled with 1 / 2 volume of anhydrous ethanol (purity ≥99vol.%) and 1 / 2 volume of high-purity argon (purity ≥99.999vol.%). The mixed target powder is placed in a vacuum drying oven for high-temperature and vacuum drying. The drying temperature is set to 150°C, the vacuum pressure is set to -0.1MPa, the heating rate is 80°C / min, the insulation time is 1h, and then the temperature is reduced to 25°C for storage. The obtained powder material is placed in a vacuum bag for vacuum storage for standby use;
[0115] S2. The SLM method is used to first form the AZ91D magnesium alloy, and then the surface powder is removed from the entire substrate using an ultrafast laser. The laser power of the ultrafast laser is 20W, the pulse frequency is 10kHz, the travel speed is 800cm / s, and the overlap rate is 50%. The femtosecond laser is used to process dot matrix holes on the surface of the AZ91D magnesium alloy substrate. The hole diameter is 20μm, the depth is 5μm, and the minimum spacing between two holes is 1 hole diameter. The femtosecond laser power is 30W, the pulse frequency is 20kHz, and the travel speed is 200cm / s.
[0116] S3. The powder obtained by S1 is spread on the surface of the substrate obtained by S2, and is spread evenly in a manner of filling the microstructure. A ceramic scraper is used to repeatedly spread the mixed powder to ensure that the nanoparticles can completely fall into and fill the deep pits ablated by the ultrafast laser. At the same time, the micron powder can also be evenly spread on the surface of the substrate to be protected. The thickness of each layer of powder is set at 40μm. SLM continuous laser is used for forming, and the scanning strategy is selected as a zigzag scanning method; the SLM continuous laser power is 100W, the scanning speed is 500mm / s, and the scanning interval is 0.04mm; an ultrafast laser is used for full-width rapid scanning to smooth the SLM surface. The ultrafast laser power is 20W, the pulse frequency is 10kHz, the walking speed is 800cm / s, and the overlap rate is 50%.
[0117] S4. Repeat the above steps S2 and S3 until the desired coating thickness is reached, thereby obtaining the active metal surface coating.
[0118] Compared with Example 1, the main difference of this comparative example is that no nanoparticles are added.
[0119] The parameters of each embodiment and comparative example are shown in Table 1 below:
[0120] Table 1 Setting parameters of Examples 1-4 and Comparative Examples 1-7
[0121]
[0122]
[0123] The functional coating on the surface of the active metal material of Example 1 was characterized and analyzed, and the results are as follows:
[0124] Figure 2 For this application, the microstructure diagram of the functional coating on the surface of the active metal material is as follows: Figure 2As shown in the figure, the nanoparticles after SLM forming are precisely distributed according to the design of the coating, and the grain structure after forming is fine. On the one hand, the nanoparticles promote the formation of equiaxed crystals in the form of nucleating agents. On the other hand, the enriched nanoparticles play a role in pinning dislocations and dispersion strengthening, thereby improving its wear resistance and corrosion resistance.
[0125] The test results of the other embodiments are basically consistent with it.
[0126] Figure 3 This is a SEM image of the active metal surface coating of Comparative Example 1 of the present invention. In Comparative Example 1, the micron powder and nanoparticles required for the target coating are mechanically mixed according to the recommended process, and the ultrafast laser fixed-point subtraction step is not performed. The mixed powder is directly formed by the SLM method. However, due to the obvious Marangoni disturbance in the molten pool during SLM forming, the nanoparticles are randomly distributed in the formed coating, and accurate distribution cannot be achieved.
[0127] Figure 4 This is a SEM image of the active metal surface coating of Comparative Example 2 of the present invention. In Comparative Example 2, the particle size of the micron powder for SLM is selected to be about 10 μm, and the other parameters remain unchanged, and then the subsequent operations are performed. Because the powder is too fine, it blocks the good filling of the nanoparticles, resulting in the inability of the nanoparticles to fill the holes processed by the femtosecond laser, promoting the formation of unmelted particles, resulting in component segregation, and ultimately failing to achieve the desired function of the coating.
[0128] Figure 5 This is a microscopic morphology of the active metal surface coating of Comparative Example 3 of the present invention. In Comparative Example 3, the particle size of the nanoparticles is limited to about 900nm, and the other parameters remain unchanged, and then the subsequent operations are performed. Since the particle size of the nanopowder is too large, there are a large number of pores in the formed coating surrounding the reinforcing particles, which significantly reduces the hardness and corrosion resistance of the coating, and cannot achieve the required function of the coating.
[0129] Figure 6 This is a microscopic morphology of the active metal surface coating of comparative example 4 of the present invention. In comparative example 4, the setting of the femtosecond subtractive process parameters exceeds the recommended range, specifically laser power = 5W, pulse frequency = 1kHz, travel speed = 600cm / s, and the other parameters remain unchanged. Due to the low output energy density of the femtosecond laser, the holes on the surface after laser ablation are not of the same size and not deep enough due to insufficient energy, which makes it difficult to meet the forming requirements of the SLM coating.
[0130] Figure 7 is a microscopic morphology of the active metal surface coating of Comparative Example 5 of the present invention. Due to the excessive laser power used in Comparative Example 5, Figure 7As shown in the figure, the impacted holes are not only deep and wide, but also have a wider melt width. In addition, the pulse frequency used is too high, resulting in a narrow interval between adjacent holes. Some holes are even directly covered, resulting in the inability to make the nanoparticles fall into the desired holes regularly during the next powder spreading process. Instead, they are concentrated in the overlapping areas of the holes in large flakes, ultimately leading to the failure of coating formation.
[0131] Figure 8 This is a macro-microscopic morphology of the active metal surface coating of Comparative Example 6 of the present invention. In Comparative Example 6, the setting of the SLM additive process parameters exceeds the recommended range, specifically when the laser power is 200W, the scanning speed is 50mm / s, and the scanning spacing is 0.02mm, the SLM-formed coating surface has obvious bulging due to the excessive energy density input, and the coating has a large number of holes and even cracks inside due to the excessive energy density, which makes it difficult to meet the use requirements of the SLM-formed coating.
[0132] The performance tests were performed on Examples 1 to 4 and Comparative Examples 1 to 7. The specific test methods are as follows:
[0133] Friction performance test
[0134] The average microhardness test of the SLM coating samples prepared in Examples 1 to 4 was performed as follows: the Vickers microhardness of the sample was measured using a microhardness tester (model: Leitz Wetzlar, Germany), the load used was 100 g, and the loading time was 20 s. The surface roughness of the SLM sample test surface was polished to less than 0.15 μm, and the microhardness values of different positions on the surface of the SLM-formed coating sample were measured, and the average value was taken after 10 measurements.
[0135] Biological performance testing
[0136] The SLM coating samples prepared in Examples 1 to 4, the coating samples prepared in Comparative Example 7, the SLM-molded AZ91D and the cast AZ91D samples were subjected to in vitro cytotoxicity, proliferation and differentiation analysis using MC3T3-E1 osteoblast precursor cells in accordance with the international standard ISO 10993-5. Before use in the cytotoxicity test, a liquid extract of the sample was prepared (37°C, containing 10% FBS (v / v), 3 cm in α-MEM 2 / mL) and sterilized by filtration, and the cytotoxicity was evaluated using a cell counting kit-8 (CCK-8). BMSCs were plated at 1×10 4The density of 10 cells was inoculated on a 96-well plate for one day, and then the liquid extract of α-MEM (positive control, providing reproducible cytotoxicity) containing 10% FBS (v / v) and 10% dimethyl sulfoxide (DMSO) and the liquid extract of the sample from each group (100 μL / well) were replaced with the culture medium for 1 day, 3 days, 5 days and 7 days. Subsequently, 10 μL of CCK-8 solution was added to each well of the plate, and the plate was incubated for two hours under illumination. The absorbance at 450 nm was measured. The values of the negative control wells were averaged and used as 100% cell viability. All other values were then averaged relative to their groups and compared with the negative control group.
[0137] The SLM coating samples prepared in Examples 1 to 4, the coating samples prepared in Comparative Example 7, the SLM-molded AZ91D and the cast AZ91D samples were tested for anti-Staphylococcus aureus, and the test method was as follows:
[0138] LB liquid culture medium: Use a measuring cylinder to measure 100 mL of distilled water and pour it into a 250 mL reagent bottle. Use an analytical electronic balance to weigh 2.5 g of LB broth culture medium and add it to mix well. Sterilize it in a high-temperature and high-pressure steam sterilizer at 121°C for 15 minutes and set aside for use.
[0139] LB solid culture medium - use a measuring cylinder to measure 100mL of distilled water and pour it into a 250mL reagent bottle. Use an analytical electronic balance to weigh 2.5g of LB broth culture medium and 1.5g of agar powder respectively. Add the above weighed reagents and mix well. Sterilize in a high-temperature and high-pressure steam sterilizer at 121℃ for 15min. When the culture medium cools to about 40-50℃, use an electric pipette to draw 15mL of culture medium and pour it into a disposable sterile plate.
[0140] Take two 12mL bacterial culture tubes, add 3mL LB liquid medium to each, pick a single colony from the solid culture medium of Staphylococcus aureus and add it to the liquid culture medium, and use the other tube as a blank control. Place in a constant temperature shaker (37℃, 200rpm) and shake culture overnight (15h).
[0141] Wipe the surface of the sample with 75% alcohol cotton, and after drying, place it in a disposable culture dish with the corresponding number, sterilize it with ultraviolet light on both sides for 30 minutes, and set aside.
[0142] Dilute Staphylococcus aureus to 106 CFU / mL with LB liquid medium. Add 50 μL of diluted bacterial solution to the sample surface, and do not add sample to the control group. Cover with a cover film and press gently. Place in a constant temperature incubator at 37°C and culture for 18 hours.
[0143] After the culture is completed, rinse with 2 mL of sterile PBS, and dilute it 10 times with PBS solution, and evenly spread 100 μL of the dilution on the LB solid medium. Incubate it in a 37°C constant temperature incubator for 18 hours, take it out, take pictures and record the number of colonies. Then count the colonies and calculate the antibacterial rate according to GB4789.2-2016.
[0144] Fig. 9 1 is a cell staining diagram of Example 1 of the present invention and the AZ91D sample formed by SLM. Fig. 9 As shown, the left is the leachate of the SLM-molded AZ91D sample, and the right is the leachate of Example 1 of the present invention. When the leachate of the materials treated and untreated by the present method is immersed for 1 day and is used to culture MC3T3-E1 osteoblasts, it can be found that more cells in the coating survive, while a small amount of dead cells appear in the untreated material. The reason for this is that on the one hand, the material without coating protection degrades faster, resulting in a higher pH value in the leachate, which is alkaline and not conducive to cell growth; on the other hand, since there is no Cu, Zn ions in the coating that can promote osteoblast growth in the matrix, live and dead cell staining found that a small amount of dead cells appeared in the material not treated by the present method.
[0145] Fig.10 1 is an antibacterial effect diagram of Example 1 of the present invention and Comparative Example 7. Fig.10 As shown, the left is the leachate of comparative example 7, and the right is the leachate of embodiment 1 of the present invention. After the coating leachate prepared by the present method was co-cultured with Staphylococcus aureus for 7 days, the antibacterial effect containing nano ZnO and CuO was significantly improved compared with the control group. This is because the nano oxides can penetrate the surface membrane of the bacteria and enter the bacteria to exert their effects, thereby killing the bacteria. Therefore, their antibacterial properties are significantly improved, while the antibacterial effect of the material leachate without nano particles is relatively general.
[0146] The specific results are shown in Table 2 below:
[0147] Table 2 Test results of Examples 1-4 and Comparative Example 7, SLM-molded AZ91D and cast AZ91D
[0148]
[0149]
[0150] It can be seen from the above table that the hardness of the functional coating samples on the surface of active metal materials prepared by various embodiments of the present invention is about 10% to 88% higher than that of traditional and SLM formed, and the average friction coefficient is reduced by about 50%. At the same time, the degradation rate, antibacterial property and cell survival rate of the coating are significantly improved compared with the parts prepared by traditional methods. It is an innovative channel for achieving simultaneous promotion of mechanical and biological properties, and provides excellent potential and good application prospects for magnesium alloy medical devices in surface protection and functionalization.
[0151] The hardness, wear resistance and biological properties of the coating prepared in Comparative Example 7 without adding nanoparticles are basically the same as those of the coating formed directly by SLM. The average hardness of the SLM AZ91D sample is 90.2±3.37HV 0.1 The friction and wear coefficient is 0.44±0.055, while the average hardness of the coating in the comparative example is only 89.5±2.81HV after 3 measurements. 0.1 The friction and wear coefficient is 0.45±0.012, and other physical and chemical properties are basically the same, and do not play a greater strengthening role.
[0152] In summary, the present invention prepares the functional coating on the surface of active metal materials by alternating ultrafast laser fixed-point subtraction and SLM and other technologies, which is convenient, fast, simple, efficient and can be flexibly used. The prepared coating has few defects such as pores and cracks, and the grains are extremely fine. It is mainly composed of dense equiaxed crystal structure and is metallurgically bonded to the matrix. The added nanoparticles not only play the role of in-situ nucleating agents to promote grain refinement and dispersion strengthening, but also because of the precise distribution of nanoparticles inside the coating, it can provide a reliable method for the controllable degradation and biological function expression of the coating. While achieving the improvement of hardness and mechanical effects such as particle enhancement and in-situ strengthening, it also realizes the controllable release of functional nanoparticles. The obtained coating can achieve controllable thickness and metallurgical bonding. The nanoparticles are accurately distributed inside the coating according to the designer's ideas, and the required coating efficacy can be expressed in sequence according to the designer's ideas, meeting its application needs in high-end medical and other fields.
[0153] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for accurately preparing functional coatings on the surface of active metal materials by adding or subtracting materials, characterized in that: The following steps are involved: S1. Select micron powder with a particle size of 20 to 75 μm and nanoparticles with a particle size of 10 to 500 nm, mix them evenly, vacuum dry them, and set aside; S2. Processing microstructures on the substrate surface using an ultrafast laser; the ultrafast laser power is 10 to 60 W, the pulse frequency is 5 to 50 kHz, and the travel speed is 100 to 500 cm / s; S3. The mixed powder obtained in S1 is laid on the surface of the substrate obtained in S2, evenly laid in a manner to fill the microstructure, and formed by SLM continuous laser; the SLM continuous laser power is 50 to 150 W, the scanning speed is 100 to 800 mm / s, and the scanning interval is 0.03 to 0.05 mm; S4. Repeat the above steps S2 and S3 until the desired coating thickness is reached, thereby obtaining the functional coating on the surface of the active metal material.
2. A method for accurately preparing functional coatings on the surface of active metal materials by adding or subtracting materials according to claim 1, characterized in that: The ratio of the micron powder and the nanoparticles in S1 is (80-95):(5-20).
3. A method for accurately preparing functional coatings on the surface of active metal materials by adding or subtracting materials according to claim 1, characterized in that: S1 The sphericity of the micron powder is ≥85%.
4. A method for accurately preparing functional coatings on the surface of active metal materials by adding or subtracting materials according to claim 3, characterized in that: The uniform mixing in S1 is performed by planetary ball milling; the mixing time of the planetary ball milling is 0.5 to 1.5 hours, the rotation speed is 100 to 300 r / min, and the ball-to-material mass ratio is (1 to 5):
1.
5. A method for accurately preparing functional coatings on the surface of active metal materials by adding or subtracting materials according to claim 1, characterized in that: The vacuum drying temperature in S1 is 100 to 200° C., and the pressure is -0.08 to -0.1 MPa.
6. A method for accurately preparing functional coatings on the surface of active metal materials by adding or subtracting materials according to claim 1, characterized in that: S2 The ultrafast laser is a femtosecond laser and / or a picosecond laser.
7. A method for accurately preparing functional coatings on the surface of active metal materials by adding or subtracting materials according to claim 1, characterized in that: S2 The substrate is an active metal substrate; the active metal is one or more of titanium-based materials, magnesium-based materials, iron-based materials, and zinc-based materials.
8. A method for accurately preparing functional coatings on the surface of active metal materials by adding or subtracting materials according to claim 1, characterized in that: The microstructure described in S2 is a dot matrix hole groove, the hole diameter is 3 to 20 μm, the depth is 1 to 5 μm, and the minimum distance between two holes is 1 hole diameter.
9. A method for accurately preparing functional coatings on the surface of active metal materials by adding or subtracting materials according to claim 1, characterized in that: S3 The SLM continuous laser forming also includes the step of using ultrafast laser to perform full-width rapid scanning.
10. A functional coating on the surface of an active metal material, characterized in that: The method is prepared according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for preparing magnesium silicide thermoelectric material block, device and thermoelectric material block
CN110729391A
High-activity spherical aluminum alloy with micro-nano structure as well as preparation method and application of high-activity spherical aluminum alloy
CN115041678A
Active modified spherical magnesium alloy powder based on electrostatic self-assembly as well as preparation method and application of active modified spherical magnesium alloy powder
CN115156525A
Tungsten carbide coating with surface microstructure, preparation method and application thereof, and workpiece with coating
CN110983228A
Method for manufacturing high-performance medical metal by mixing selective laser melting and laser surface texture
CN113732307A